Metabolic syndrome, intracranial arterial stenosis and cerebral small vessel disease in community-dwelling populations. Issue 4 (26th April 2021) - Shu, Mei-Jun; Zhai, Fei-Fei; Zhang, Ding-Ding; Han, Fei; Zhou, Lixin; Ni, Jun; Yao, Ming; Zhang, Shu-Yang; Cui, Li-Ying; Jin, Zheng-Yu; Zhu, Hui-Juan; Zhu, Yi-Cheng
Abstract : Background and purpose: This study aimed to investigate the association of metabolic syndrome (MetS) with both intracranial atherosclerotic stenosis (ICAS) and imaging markers of cerebral small vessel disease (CSVD) in a community-based sample. Methods: This study included 943 participants (aged 55.6±9.2 years, 36.1% male) from the community-based Shunyi cohort study. MetS was defined according to the joint interim criteria and quantified by the MetS severity Z-score. ICAS was evaluated by brain magnetic resonance angiography. The MRI markers of CSVD, including white matter hyperintensities (WMHs), lacunes, cerebral microbleeds (CMBs) and enlarged perivascular spaces (EPVS), were assessed. Multiple regression models were used to investigate the association of MetS severity Z-score with ICAS and these CSVD markers. Results: We found that risk of ICAS (OR=1.75, 95% CI 1.39 to 2.21, p<0.001) increased consistently with MetS severity. MetS severity was significantly associated with higher risks of WMH volume (β=0.11, 95% CI 0.01 to 0.20, p=0.02) and lacunes (OR=1.28, 95% CI 1.03 to 1.59, p=0.03) but not the presence of CMBs (OR=0.93, 95% CI 0.74 to 1.16, p=0.51) and PVS severity (EPVS in basal ganglia: OR=0.96, 95% CI 0.84 to 1.09, p=0.51 and EPVS in white matter: OR=1.09, 95% CI 0.96 to 1.23, p=0.21). Conclusions: Our findings suggest that WMH and lacunes share risk factors with atherosclerosis of the cerebral artery, whereas the impact of glucose and lipid metabolic disorder to CMB or EPVS might be weak.